A Meta-analysis: Effect of Tai Chi on Single-leg Standing Time of the Elderly - Xiaojun LI; Tingyu CHEN; Cui'e FENG; Jinxiu CHEN (康复学报)
Objective:To evaluate the effect of Tai Chi on one-leg standing time (OLST) of the elderly and analyze the relationships with intervention of different time.Methods:Cochrane Central Register Controlled Trials (CENTRAL), PubMed, Wanfang Data, CNKI, VIP databases were searched for the randomized controlled trials (RCTS) of the effect of Tai Chi on OLST of the elderly, from the date of establishment of the databases to January 2016. The extracted data were analyzed by RevMan 5.3.Results:A total of 6 literatures were discovered. There was one Chinese literature, others are English literatures. Meta-analyses showed that Tai Chi intervention can increase OLST. In single-leg stance with the eyes open (SLO), the effect was better than in single-leg stance with the eyes closed (SLC), and the result is [WMD=8.97, 95%CI (8.05, 9.90) ] and [WMD=5.05, 95%CI (2.72, 7.37) ] respectively. And intervention of different time had different results. The effect of Tai Chi of 3 to 4 months, 6 months and 12 months were as follows: [WMD=1.74, 95%CI (-3.75, 7.23) ], [WMD=4.58, 95%CI (2.24, 6.92) ] and [WMD=5.37, 95%CI (-0.51, 11.24) ].Conclusion:Tai Chi with varying degrees can increase OLST of the elderly and improve the static balance. And intervention of different time has different effects and at least 6 months Tai Chi exercise can promote its effects.